2000
DOI: 10.1177/0899764000293003
|View full text |Cite
|
Sign up to set email alerts
|

The Risk and Reward of a Double-Edgedsword: Effects of a Merit Payprogram on Intrinsic Motivation

Abstract: Merit pay plans are becom ing increas ingly pop u lar in non profit orga ni za tions, despite their down side risk. One risk is the poten tial neg a tive effect of the plan on employ ees' intrin sic moti va tion. The authors inves ti gated employee moti va tion in a study of a nonprofit orga ni za tion before and after the imple men ta tion of a merit pay sys tem. Results sug gest that merit pay pro duced a decline in intrin sic moti va tion for employ ees ini tially highly intrin si cally moti vated. Jus tice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 28 publications
4
37
0
4
Order By: Relevance
“…The survey data support the contention of Deckop and Cirka (2000), that intrinsic rewards have a greater impact in NFP organisations. The results also support the contention of Berry, Broadbent and Otley (1995), that people working in the caring services are more concerned with doing a worthwhile job than they are with remuneration.…”
Section: Discussionsupporting
confidence: 71%
“…The survey data support the contention of Deckop and Cirka (2000), that intrinsic rewards have a greater impact in NFP organisations. The results also support the contention of Berry, Broadbent and Otley (1995), that people working in the caring services are more concerned with doing a worthwhile job than they are with remuneration.…”
Section: Discussionsupporting
confidence: 71%
“…These kinds of rewards are distinct from the external motivation offered in exchange for work tasks, such as knowledge contribution. Other studies have also found that there is a negative relationship between external motivation and intrinsic motivation (Eden, 1975), and that the introduction of external rewards can undermine intrinsic motivation (Deckop and Cirka, 2000). While several laboratory experiments have supported the negative relationship between external and intrinsic motivation (Deci et al, 1999;Mossholder, 1980), Gagne and Deci (2005) have called for an examination of this relationship in organizations.…”
Section: Intrinsic Motivation and External Motivationmentioning
confidence: 99%
“…Empirical evidence of overjustification and crowding-out effects (cf., Frey & Jegen, 2001) is provided by Deckop and Cirka (2000) in their quantitative study of the effects of a merit pay program on intrinsic motivation at a nonprofit religiously affiliated college. Using data collected at two time periods, their research reveals a crowding-out of intrinsic motivation for the employees who had a high intrinsic motivation before the merit pay program and who experienced an increase in control by pay.…”
Section: Different Needs and Motivationmentioning
confidence: 99%
“…In line with Moore (2003), however, the direct transferal of for-profit strategic management models to nonprofits ignores the fact that these financial measures of performance do not take the social goals of NPOs and their employees into account. For example, research shows that managers in a nonprofit religiously affiliated college ignored the motivational background and individual goals of their HR base by implementing pay for performance plans without considering the potential negative effects on intrinsic motivation (Deckop & Cirka, 2000).…”
Section: Strategic Hrmmentioning
confidence: 99%